De Gruyter Handbook of Entrepreneurial Finance - Lingelbach, David (De Gruyter Handbooks in Business, Economics and Finance Ser., 2022)
De Gruyter Handbooks in Business, Economics and Finance provide a comprehensive, must-have survey of a whole subject area critically discussing the leading views in the field. The main goal of each handbook is to survey a topic, explaining why an issue is important and critically discussing the leading views in the area. Aimed at the international market, these handbooks cover emerging and cutting edge topics in business, economics and finance.